THE LEGAL ASPECTS OF SUICIDE - Tonél, Rodrigo; Sturza, Janaína Machado; Dilkin, Rogério De Almeida; Berwig, Aldemir; Gagliardi, André; Biguelini, Thais (Salão do Conhecimento, 2017)
Interdisciplinary research developed by the Department of legal and social sciences - DCJS/UNIJUI.